1987
DOI: 10.1016/0043-1354(87)90071-6
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic degradation of nonionic and anionic surfactants in enrichment cultures and fixed-bed reactors

Abstract: Abstract--Anaerobic biodegradation and inhibitory effects of nonionic and anionic surfactants on methanogenic fermentation were tested in incubation experiments with anoxic sediment samples and sewage sludge. Alkylsulfonates and alkylbenzenesulfonates were not degraded but inhibited methanogenesis from sludge constituents at concentrations 1> 10 mg l-k Sodium dodecylsulfate was at least partly degraded after adaptation at concentrations ~< 100 mg 1 -~ and the sulfate group was reduced to sulfide. The polyethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 27 publications
2
34
0
5
Order By: Relevance
“…Numerous studies regarding AS degradation have used AS concentrations ജ20,000 g/liter (Anderson et al, 1990;Marchesi et al, 1991;Russell et al, 1991;Vives-Rego et al, 1987;Wagener and Schink, 1987). However, Fendinger et al observed only ഛ700 g/liter in sewage influent and were unable to detect AS in receiving streams downstream of two trickling filter sewage treatment plants (detection limit <10 g/liter) (Fendinger et al, 1992).…”
Section: Introductionmentioning
confidence: 94%
“…Numerous studies regarding AS degradation have used AS concentrations ജ20,000 g/liter (Anderson et al, 1990;Marchesi et al, 1991;Russell et al, 1991;Vives-Rego et al, 1987;Wagener and Schink, 1987). However, Fendinger et al observed only ഛ700 g/liter in sewage influent and were unable to detect AS in receiving streams downstream of two trickling filter sewage treatment plants (detection limit <10 g/liter) (Fendinger et al, 1992).…”
Section: Introductionmentioning
confidence: 94%
“…[18] There are only few reports on the effects of LAS on the specific methanogenic activity (SMA). Wagener and Schink [19] found methane production inhibition rates of 18% and 84% at LAS concentrations of 10 and 100 mg L ¡1 , respectively. The authors suggested that the action of the surfactant in cells is complex and that it includes the penetration and fluidization of the membrane and the solubilization of structural components.…”
Section: Introductionmentioning
confidence: 98%
“…Linear alkylbenzene sulfonate (LAS) are the most common synthetic anionic surfactants used as domestic and industrial detergent (Gavala and Ahring, 2002;Ying, 2006) and are very difficult to be degraded under anaerobic conditions because of their high toxicity to acetoclastic methanogens (Wagner and Schink, 1987;García-Morales et al, 2001). This inference was drawn based on the fact that inhibition of methanogenesis was accompanied by the accumulation of acetate (Shcherbakova et al, 1999).…”
Section: Introductionmentioning
confidence: 99%